MOTIVATION OF SALES MARKETING EMPLOYEE WORK AT COMFORT HOTEL DUMAI - Tutut Dia Ambarani; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Responses in the world of tourism are the opinions or point of view of visitors and tourists in understanding a tourist destination. This research was conducted at the Comforta Hotel Dumai located at jl. jend. Sudirman no. 58, Dumai- Riau- Indonesia. This study aims to determine the responses of sales marketing employees at the Comforta Hotel Dumai. This study uses a Quantitative Descriptive method to process data obtained in the field through interviews, observations, questionnaires and documentation study all information collected and studied so that it becomes a complete unit (Sugiono. 2000). Whereas for the sample in the study as many as 3 respondents, the data collection techniques used were observation, interviews, questionnaires and documentation study using a likert scale as a measuring tool. Based on the results of research that has been done, the response of sales marketing employees at the Comforta Hotel Dumai with sub-variables of Physical Needs(86,6%), Security Needs (50,0%), Social Needs(90,0%), Appreciation Needs (66,6%) and Self-actualization Needs (83,3%) with good research conclusions.  Keywords: Motivation, Sales marketing, Hotel